2023
DOI: 10.3389/fcell.2022.1060440
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pubertal oocytes harbor altered histone modifications and chromatin configuration

Abstract: Pre-pubertal oocytes are still dormant. They are arrested in a GV state and do not undergo meiotic divisions naturally. A multitude of molecular pathways are changed and triggered upon initiation of puberty. It is not yet clear which epigenetic events occur in oocytes upon pubertal transition, and how significant these epigenetic events may be. We evaluated epigenetic marker levels in mouse pre-pubertal and post-pubertal female oocytes. In addition, we evaluated H3K9me2 levels in human oocytes collected from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…All these genes are important for oocyte function (Yuan et al, 2019). Moreover, our own results show the existence of an extensive chromatin remodeling event that occurs in mouse and human oocytes (mouse‐ at 19 days, human‐ before onset of menstrual bleeding) upon exposure to FSH during the pubertal transition (Wasserzug‐Pash et al, 2023). This event also manifests in changes of histone modification patterns, but the specific details are still in need of further investigation.…”
Section: Oocyte Agingmentioning
confidence: 80%
See 1 more Smart Citation
“…All these genes are important for oocyte function (Yuan et al, 2019). Moreover, our own results show the existence of an extensive chromatin remodeling event that occurs in mouse and human oocytes (mouse‐ at 19 days, human‐ before onset of menstrual bleeding) upon exposure to FSH during the pubertal transition (Wasserzug‐Pash et al, 2023). This event also manifests in changes of histone modification patterns, but the specific details are still in need of further investigation.…”
Section: Oocyte Agingmentioning
confidence: 80%
“…The epigenome may also change in resting oocytes during the pubertal transition. Hormonal exposure of the oocytes and surrounding niche cells, as well as structural changes that the ovary itself undergoes during puberty may trigger nuclear and epigenetic changes in mouse and human oocytes (Karavani et al, 2021; Kusuhara et al, 2021; Wasserzug Pash et al, 2023). Previous work has shown that DNA methylation changes during puberty in pig ovaries (at 160 days of age), in promoters of genes that are related to PI3K‐Akt signaling pathway, GnRH signaling pathway, and insulin secretion.…”
Section: Oocyte Agingmentioning
confidence: 99%
“…Consistent with this, it has been demonstrated that inhibition of reverse-transcriptase activity or artificially increasing heterochromatin levels in aging oocytes abrogates DNA damage and improves oocyte in-vitro maturation efficiency when applied to aged oocytes [ 19 ]. In addition, post-translational histone modifications (PTMs) modulate transcriptional activity [ 21 ] in the egg and, as part of their meiotic function, they are of importance for the processes of kinetochore formation and chromosome segregation [ 22 ]. Noteworthy, changes in histone PTM patterns and DNA methylation are typical for oocyte oogenesis and maturation [ 23 ], and appear to be sensitive in response to stress, stimulation, and aging [ 22 ].…”
Section: Epigenetic Alterations As a Hallmark Of Oocyte Development A...mentioning
confidence: 99%
“…In addition, post-translational histone modifications (PTMs) modulate transcriptional activity [ 21 ] in the egg and, as part of their meiotic function, they are of importance for the processes of kinetochore formation and chromosome segregation [ 22 ]. Noteworthy, changes in histone PTM patterns and DNA methylation are typical for oocyte oogenesis and maturation [ 23 ], and appear to be sensitive in response to stress, stimulation, and aging [ 22 ]. A recent study provided evidence that the chromatin structure in post-pubertal murine oocytes has fewer chromocenters than prepubertal counterparts, and heterochromatin marker values, such as H3K9me2, H3K27me3, or H4K20me1 increase significantly at the onset of puberty [ 22 ].…”
Section: Epigenetic Alterations As a Hallmark Of Oocyte Development A...mentioning
confidence: 99%
See 1 more Smart Citation